Trypanosome infection rates in tsetse flies in the "silent" sleeping sickness focus of Bafia in the Centre Region in Cameroon. Issue 1 (December 2015) - Simo, Gustave; Fongho, Pierre; Farikou, Oumarou; Ndjeuto-Tchouli, Prosper; Tchouomene-Labou, Judith; Njiokou, Flobert; Asonganyi, Tazoacha
Abstract Background The Bafia sleeping sickness focus of Cameroon is considered as "silent" with no case reported for about 20 years despite medical surveys performed during the last decades. In this focus, all epidemiological factors that can contribute to trypanosomes transmission are present. To update our knowledge on the current risks of Human and Animal African trypanosomiases, different trypanosome species were identified in midguts of tsetse flies captured in the Bafia focus. Methods Tsetse flies were trapped using pyramidal traps. Each tsetse fly was identified and live flies were dissected and their midguts collected. DNA was extracted from each midgut and thereafter, blood meals and different trypanosome species were identified with molecular tools. The biological data were transported onto maps in order to have their distribution. Results Of the 98 traps set up, 461Glossina palpalis palpalis were captured; 322 (69.8 %) tsetse flies were dissected and 49 (15.2 %) teneral flies identified. The average apparent density of tsetse flies per day was 1.18. Of the 35 (10.9 %) blood meals collected, 82 % were taken on pigs and 17.6 % on humans. Eighty two (25.5 %) trypanosome infections were identified: 56 (17.4 %)T. congolense savannah, 17 (5.3 %)T. congolense forest, 5 (1.6 %)T. vivax and 4 (1.2 %)T. brucei s.l. No infection ofT. simiae andT. b. gambiense was identified. Sixty seven (81.7 %) infections were single and 15 (18.3 %) mixed involving one triple infection (T. congolense forest, T. brucei andT. vivax ) and 14 double infections: 11 T. congolense forest andT. congolense savannah, twoT. congolense savannah andT. brucei, and one ofT. brucei andT. vivax . The generated maps show the distribution of tsetse flies and trypanosome infections across the focus. Conclusion This study has shown that animal trypanosomes remain an important problem in this region. Meanwhile, it is very likely that HAT does not seem anymore to be a public health problem in this focus. The generated maps enabled us to define high risk transmission areas for AAT, and where disease control must be focused in order to improve animal health as well as the quantity of animal proteins.